Growth and yield of sweet corn intercropping with caisim of different plant densities and planting times - Titin Sumarni; Naufal Ammar Nabil; Ariek Dwi Anggoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Intercropping of sweet corn and caisim is an effort to improve land efficiency. The study aimed to determine the land use optimization of intercropping between sweet corn and caisim from different plant densities and planting times. Research was carried out from May to July 2024, in Bocek Village, Malang, East Java. The study used a randomized complete block design with a single factor consisting of 7 treatments, i.e., monoculture sweet corn, and sweet corn + caisim (1 and 2 rows) planted 7 days before, at the same time, and 7 days after planting corn. Results showed that all intercropping treatments resulted in R/C ratio and LER values > 1, with the highest values observed of sweet corn + caisim of 1 row planting at the same time. The R/C ratio was 1.22 and the LER was 1.35, indicating that land use was optimized without causing a decline in growth or production for either crop. Keywords: cropping system, LER, number of rows, R/C ratio, Zea mays